Detectability of corrosion damage with circumferential guided waves in reflection and transmission. (October 2017) - Howard, Richard; Cegla, Frederic
Abstract: There is an increasing interest in high frequency short range guided waves to screen or monitor for corrosion. This contrasts with long range guided waves (LRGWs) which screen pipes for large patches of corrosion and have been successfully used in corrosion management for the past twenty years. The fundamental setup described in this paper uses circumferential guided waves, which are excited at a single location on a pipe and travel around the pipe wall and are detected at the same location. The study uses a finite element model assisted method to evaluate the detection capability of two short range circumferential guided wave setups which use both the reflected and transmitted signals. The setups themselves consist of either an axial array of transducers, for monitoring, or a single transducer which axially scans a pipe. Both setups have an array or scan pitch between either adjacent transducers or measurements. The detection capability of the fundamental Lamb wave modes (A0 and S0) in both reflection and transmission have been compared, as well as a hybrid shear horizontal wave setup, which uses the SH0 mode in reflection and the SH1 mode in transmission. A sensitivity analysis was conducted using two separate methods to determine the probability of detection (POD) for either the reflection or transmission signals. Both methods determine a POD for a specific defect, noise level, and array or scan pitch. Probability images are produced which map the POD for a range of defect sizes. For the parameters investigated in this study, it was found that in transmission large diameter defects have a higher detectability, whereas deep, narrow diameter defects are more detectable in reflection. A generalised overview of the sensitivity of short range guided waves is presented by combining both the reflection and transmission PODs. The data fused sensitivity of the S0 and SH hybrid modes are given as 0.6% and 0.75% cross sectional area (CSA) respectively, allowing for the comparison with LRGWs. The A0 mode was excluded from the POD analysis because it was much less sensitive than the other two modes.